Pengaruh Internet dan Media Sosial Terhadap cara Mencapai Kekudusan Kaum Muda Katolik di Paroki Santo Vinsensius A Paulo, Malang - Nikodemus Nikodemus; Yohanes Endi (BADAN PENERBIT STIEPARI PRESS, 2024)
This study pays attention to the Influence of the Internet and Social Media on the way of centering the Holiness of the Youth of the Parish of Saint Vincentius A Paulo, Malang. The author's observation of several human phenomena that experience a crisis of faith due to social media. This study uses a qualitative approach and the type of research is a questionnaire (questionnaire). This qualitative approach was chosen because the authors assume that using this approach can describe the problem under study as a whole. The author distributes a questionnaire with fourteen (14) questions. This question is divided into two parts, the first question is answered directly, the second question is answered using a brief explanation. The research data was distributed to OMK (Young Catholics) of St. Vincentius A Paulo Parish, Malang. The process and analysis used in this research is an interactive data analysis model by Miles and Huberman. The analysis consists of four stages, namely data collection, data reduction, data presentation, and conclusion and verification. The results of the research on the Holiness of Catholic Youth, the Identity of Catholic Youth, and the Influence of the Internet on Catholic Youth.